Changes in sediment and organic carbon accumulation in a highly-disturbed ecosystem: The Sacramento-San Joaquin River Delta (California, USA) - Canuel, E. A.; Lerberg, E. J.; Dickhut, R. M.; Kuehl, S. A.; Bianchi, T. S.; Wakeham, S. G. (Marine Pollution Bulletin, 2009)
We used the Sacramento-San Joaquin River Delta CA (Delta, hereafter) as a model system for understanding how human activities influence the delivery of sediment and total organic carbon (TOC) over the past 50-60 years. Sediment cores were collected from sites within the Delta representing the Sacramento River (SAC), the San Joaquin River (SJR), and Franks Tract (FT), a flooded agricultural tract. A variety of anthropogenic tracers including (CS)-C-137, total DDE (Sigma DDE) and brominated diphenyl ether (BDE) congeners were used to quantify sediment accumulation rates. This information was combined with total organic carbon (TOC) profiles to quantify rates of TOC accumulation. Across the three sites, sediment and TOC accumulation rates were four to eight-fold higher prior to 1972. Changes in sediment and TOC accumulation were coincident with completion of several large reservoirs and increased agriculture and urbanization in the Delta watershed. Radiocarbon content of TOC indicated that much of the carbon delivered to the Delta is "pre-aged" reflecting processing in the Delta watershed or during transport to the sites rather than an input of predominantly contemporary carbon (e.g., 900-1400 years BP in surface sediments and 2200 yrs BP and 3610 yrs BP at the base of the SJR and FT cores, respectively). Together, these data suggest that human activities have altered the amount and age of TOC accumulating in the Delta since the 1940s. (C) 2009 Elsevier Ltd. All rights reserved.
id: 1845; Sp. Iss. SI 477XX Times Cited:1 Cited References Count:49Y

Partitioning of organic matter in continental margin sediments among density fractions - Wakeham, S. G.; Canuel, E. A.; Lerberg, E. J.; Mason, P.; Sampere, T. P.; Bianchi, T. S. (Marine Chemistry, 2009)
Hydrodynamic processes sort and redistribute organic matter (OM) and minerals on continental margins. Density fractionations were conducted on sediments from diverse margins (Mexico margin, Gulf of Mexico, Mississippi River delta, Eel River margin) to investigate the nature, provenance and age of OM among density fractions. Mass. elemental (C and N), lignin, and surface area distributions, as well as stable carbon and radiocarbon isotopic compositions were measured, The lowest density fractions (2.5 g cm(-3)) were OC-poor (%OC -200 parts per thousand). Ratios of vanillic acid to vanillin (Ad/Al)v among lignin oxidation products increase with increasing particle density suggesting variable lignin sources or selective degradation of lignin among the different density fractions. (C) 2009 Elsevier B.V. All rights reserved.
id: 1844; 521ZI Times Cited:0 Cited References Count:99Y